Communal and Community-Forming Character of Prayer - Tatar, Marek (Collectanea Theologica, 2021)
In the age of secularisation, prayer is becoming an increasingly difficult act of believers to understand. Extremely dangerous individualism and subjectivism is the contemporary threat to common and community prayer. All of this makes it necessary to take a new look at this category of prayer so that it leads to an authentic testimony from Christians in the world. In this way, it also prevents the dangerous exclusivity of believers themselves when faced with challenges. Among the whole variety and categories of prayers, communal prayer and the prayer of community are very important. This distinction is necessary because it reveals to us the truth that every prayer has a communal character even though it is not always a common prayer. However, prayer celebrated together is the source of life for the Christian, the Church and the clearest and most readable testimony of faith.